On the study of analogues in cosmic magnetism - Adams, Patrick William (Department of Statistical Sciences, 2018)
The dynamo process, by which the strength of the magnetic field is amplified, is still not well understood and, in part, requires an understanding of the behaviour of the plasma fluid (i.e. a charged fluid) in different conditions. It has long been known that charged and non-charged fluids display similar behaviour to each other, with key quantities such as the magnetic field, B, and fluid vorticity, ω, being both structurally-similar and playing similar roles to each other in their respective evolution equations.